Мікробіологічні особливості розподілу патогенів та антибіотикорезистентність при позалікарняних пневмоніях ускладненого перебігу у дітей раннього і дошкільного віку - Курочкін, Михайло Юрійович; Давидова, Анна Григорівна; Курочкин, М. Ю.; Давыдова, А. Г.; Городкова, Ю. В.; Kurochkin, M. Yu.; Davydova, A. G; Horodkova, Yu. V. (My University, 2019)
Резюме. Проведений аналіз результатів мікробіологічних досліджень (398 зразків) у 87 дітей раннього і дошкільного віку з позалікарняною пневмонією ускладненого перебігу (ППУП), що потребували інтенсивної терапії в місті Запоріжжі. Виявлено: найбільш розповсюдженими етіологічними бактеріями у даних категоріях дітей слід вважати стрептококи, серед яких переважає Str.pneumoniae. Локальний патерн резистентності найбільш поширених етіологічних збудників виявлений до незахищених пеніцилінів, макролідів, цефалоспоринів 1-го покоління, лінкозамідів; розроблені алгоритми емпіричної антибактеріальної терапії. Фактором ризику полірезистентної інфекції при надходженні до лікарні у дітей раннього і дошкільного віку з ППУП є наявність гострих інфекційних захворювань у попередні 3 міс. Резюме. Проведен анализ результатов микробиологических исследований (398 образцов) у 87 детей раннего и дошкольного возраста с внегоспитальной пневмонией осложненного течения (ВПОТ) в городе Запорожье, которым была необходима интенсивная терапия. Выявлено, что наиболее распространенными этиологическими бактериями в данных категориях детей следует считать стрептококки, среди которых преобладает Str.pneumoniae. Локальный паттерн резистентности наиболее распространенных этиологических возбудителей выявлен к незащищенным пенициллинам, макролидам, цефалоспоринам 1-го поколения, линкозамидам; разработаны алгоритмы эмпирической антибактериальной терапии. Фактором риска полирезистентной инфекции при поступлении в больницу у детей раннего и дошкольного возраста с ВПОТ является наличие острых инфекционных заболеваний в предыдущие 3 мес. Abstract. The widespread of acute pneumonia is a major threat to children. Knowledge on the local epidemiology and antibiotic resistance pattern is a platform in improving the empiric antibiotic therapy. The aim of the work – to increase the effectiveness of intensive care (IC) in children aged 1-7 years old with complicated community-acquired pneumonia (CAP) by substantiating empiric antibiotic therapy; to evaluate the microbiological peculiarities of the pathogens’ distribution at the local level and assessing its antibiotic sensitivity in conjunction with clinical characteristics. Object and methods. It is a retrospective analysis, cohort study, one-centred research. From 2002 through 2018, we enrolled children aged 1-7 years old with complicated community-acquired pneumonia (CAP) (4-th and 5-th degree of severity), hospitalized at pediatric intensive care unit (PICU) in the Municipal Children’s Hospital (MCH) №5, Zaporizhzhia, Ukraine. Group I included children with discrete plasmapheresis usage in complex IC, group II – children who received baseline therapy (BT). Each of the groups were divided into subgroups: A – children aged 1-3 years old, B – children aged 3-7 years old. The studies were carried out in the bacteriological laboratory of MCH № 5, using the standard disco-diffusion method for determining the sensitivity of microorganisms to antibiotics with the evaluation of the results by EUCAST 2016 criteria. MRSA was determined in the test with oxacillin or cefoxitin. Samples from the upper respiratory tract (pharynx, nose), lower respiratory tract (tracheo-bronchial swabs), pleural punctate were studied. 398 samples were analyzed.
Микробиологические особенности распределения патогенов и антибиотикорезистентность при внебольничных пневмониях осложненного течения у детей раннего и дошкольного возраста
Microbiological peculiarities of pathogens’ distribution and antibiotic resistance in children Aged 1-7 years old with complicated community-acquired pneumonia
Keywords: пневмонія; діти; плазмаферез; антибактеріальні препарати; антибактеріальна резистентність.; пневмония; дети; плазмаферез; антибактериальные препараты; антибактериальная резистентность; pneumonia; child; plasmapheresis; anti-bacterial agents; antibacterial drug resistance